Answer:
Therefore
[tex]\sin (a+b) =-\dfrac{23}{65}[/tex]
Step-by-step explanation:
Given:
[tex]\sin a =\dfrac{12}{13}\\\\\cos b=-\dfrac{4}{5}[/tex]
To Find:
[tex]\sin (a+b)= ?[/tex]
Solution:
Using identity,
[tex]\sin^{2}a+\cos^{2}a=1[/tex]
Now Substitute Sin a we get
As 'a' is in Second Quadrant Cos a is Negative
Similarly,
[tex]\sin^{2}b+\cos^{2}b=1[/tex]
Now Substitute Cos b we get
[tex](\dfrac{-4}{5})^{2}+\sin^{2}b=1\\\\\sin^{2}b=1-\dfrac{16}{25}=\dfrac{9}{25}\\\\\sin b=\pm\sqrt{\dfrac{9}{25}}\\\\\sin b=-\dfrac{3}{5}[/tex]
As 'b' is in Third Quadrant Sin b is Negative
Now Using Identity
[tex]\sin (a+b) = \sin a.\cos b + \cos a.\sin b[/tex]
Substituting the values we get
[tex]\sin (a+b) =\dfrac{12}{13}\times -\dfrac{4}{5}+\dfrac{-5}{13}\times -\dfrac{3}{5}[/tex]
[tex]\sin (a+b) =\dfrac{-48+15}{13\times 5}[/tex]
[tex]\sin (a+b) =-\dfrac{23}{65}[/tex]
Therefore
[tex]\sin (a+b) =-\dfrac{23}{65}[/tex]